Factors associated with thiopurine non‐adherence in patients with inflammatory bowel disease. Issue 9 (15th September 2013) - Goodhand, J. R.; Kamperidis, N.; Sirwan, B.; Macken, L.; Tshuma, N.; Koodun, Y.; Chowdhury, F. A.; Croft, N. M.; Direkze, N.; Langmead, L.; Irving, P. M.; Rampton, D. S.; et al.
Summary Background Medication non‐adherence seems to be a particular problem in younger patients with inflammatory bowel disease (IBD) and has a negative impact on disease outcome. Aims To assess whether non‐adherence, defined using thiopurine metabolite levels, is more common in young adults attending a transition clinic than adults with IBD and whether psychological co‐morbidity is a contributing factor. We also determined the usefulness of the Modified Morisky 8‐item Adherence Scale (MMAS‐8) to detect non‐adherence. Methods Seventy young adults [51% (36) male] and 74 [62% (46) male] adults were included. Psychological co‐morbidity was assessed using the Hospital Anxiety Depression Scale (HADS) and self‐reported adherence using the MMAS‐8. Results Twelve percent (18/144) of the patients were non‐adherent. Multivariate analysis [OR, (95% CI), P value] confirmed that being young adult [6.1 (1.7–22.5), 0.001], of lower socio‐economic status [1.1 (1.0–1.1), <0.01] and reporting higher HADS‐D scores [1.2 (1.0–1.4), 0.01] were associated with non‐adherence. Receiver operator curve analysis of MMAS‐8 scores gave an area under the curve (95% CI) of 0.85 (0.77–0.92), (P < 0.0001): using a cut‐off of <6, the MMAS‐8 score has a sensitivity of 94% and a specificity of 64% to predict thiopurine non‐adherence. Non‐adherence was associated with escalation in therapy, hospital admission and surgeries in the subsequent 6 months of follow up. Conclusions Non‐adherence to thiopurines is more common in young adults with inflammatory bowel disease, and is associated with lower socio‐economic status and depression. The high negative predictive value of MMAS‐8 scores <6 suggests that it could be a useful screen for thiopurine non‐adherence.